Multiparametric Assessment of Vascular Function in Peripheral Artery Disease. (April 2015) - Englund, Erin K.; Langham, Michael C.; Ratcliffe, Sarah J.; Fanning, Molly J.; Wehrli, Felix W.; Mohler, Emile R.; Floyd, Thomas F.
<x xml:space="preserve">Abstract</x> Background— Endothelial dysfunction present in patients with peripheral artery disease may be better understood by measuring the temporal dynamics of blood flow and oxygen saturation during reactive hyperemia than by conventional static measurements. Methods and Results— Perfusion, Intravascular Venous Oxygen saturation, and T2* (PIVOT), a recently developed MRI technique, was used to measure the response to an ischemia–reperfusion paradigm in 96 patients with peripheral artery disease of varying severity and 10 healthy controls. Perfusion, venous oxygen saturation SvO2, and T2* were each quantified in the calf at 2-s temporal resolution, yielding a dynamic time course for each variable. Compared with healthy controls, patients had a blunted and delayed hyperemic response. Moreover, patients with lower ankle-brachial index had (1) a more delayed reactive hyperemia response time, manifesting as an increase in time to peak perfusion in the gastrocnemius, soleus, and peroneus muscles, and in the anterior compartment, (2) an increase in the time to peak T2* measured in the soleus muscle, and (3) a prolongation of the posterior tibial vein SvO2 washout time. Intrasession and intersession repeatability were also assessed. Results indicated that time to peak perfusion and time to peak T2* were the most reliable extracted time course metrics. Conclusions— Perfusion, dynamic SvO2, and T2* response times after induced ischemia are highly correlated with peripheral artery disease severity. Combined imaging of peripheral microvascular blood flow and dynamics of oxygen saturation with Perfusion, intravascular SvO2, and T2* may be a useful tool to investigate the pathophysiology of peripheral artery disease.